Web-Age Information Management 13th International Conference, WAIM 2012, Harbin, China, August 18-20, 2012. Proceedings - Gao, Hong.; Lim, Lipyeow; Wang, Wei.; Li, Chuan; Chen, Lei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 13th International Conference on Web-Age Information Management, WAIM 2012, held in Harbin, China in August 2012. The 32 revised full papers presented together with 10 short papers and three keynotes were carefully reviewed and selected from a total of 178 submissions. The papers are organized in topical sections on wireless sensor networks; data warehousing and data mining; query processing; spatial databases; similarity search and queries; XML and Web data; graph and uncertain data; distributed computing; data security and management; information extraction and integration; and social networks and modern Web services.
Keywords: Computer science; Computer Communication Networks; Data protection; Database management; Data mining; Information storage and retrieval systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Systems and Data Security; Computer Communication Networks; Information Storage and Retrieval; Information Systems Applications (incl. Internet).